2021
DOI: 10.1155/2021/8832783
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Lymphoma Masquerading as Orbital Cellulitis

Abstract: Background. Orbital lymphomas are primarily non-Hodgkin type and can originate from the eyelids, extraocular muscles, soft tissue orbital adnexa, conjunctiva, or lacrimal glands. Orbital malignancies often represent a diagnostic dilemma for clinicians given their varying and atypical presentations. Objective. To report a case of orbital lymphoma mimicking orbital cellulitis. Case. A 66-year-old male patient presented with sudden onset of painful proptosis with visual impairment in the left eye for 15 days. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Vision impairment can be caused by optic nerve infiltration or compression through mass effect. Sometimes clinical presentation can be misleading especially when symptoms overlap with those of orbital cellulitis like in our case [6].…”
Section: Case Reportmentioning
confidence: 88%
“…Vision impairment can be caused by optic nerve infiltration or compression through mass effect. Sometimes clinical presentation can be misleading especially when symptoms overlap with those of orbital cellulitis like in our case [6].…”
Section: Case Reportmentioning
confidence: 88%
“…Several studies have reported the development of EMZL in patients with rheumatoid arthritis, Sjogren's syndrome, and systemic lupus erythematosus. Infections with one of several infectious organisms have been associated with the development of EMZL, including Helicobacter pylori in gastric EMZL, Borrelia burgdorferi in skin EMZL, Chlamydia psittaci (C. psittaci) in orbital cell lymphoma, and hepatitis C virus in ocular EMZL [3,[5][6][7]. Previous studies have shown the resolution of gastric EMZL with the use of antibiotics, leading to the use of doxycycline as a treatment option for ocular EMZL.…”
Section: Discussionmentioning
confidence: 99%
“…Testing for antibodies against CD3, CD5, CD20, and CD79α to identify a lymphoma is either of B-cell or T-cell origin [ 3 ]. Additional testing to further categorize the lymphoma can also include identifying antibodies against BCL2, BCL6, CD10, CD23, CD30, Cyclin D-1, MUM-1, and κ and λ light chains [ 3 , 6 ]. A PET scan adds utility in checking for metastatic spread [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral orbital involvement, a combination of multiple therapies, and homogeneous enhancement of lesions were all associated with better outcomes. Unilateral orbit involvement was commonly found in the primary orbital lymphoma, especially for EMZL and diffuse large B-cell lymphoma, while patients with bilateral orbits involved were mainly with mantle cell lymphoma [1,9] . In this study, 21 patients had bilateral orbits involved, accounting for 20.2% of all patients, which was higher than reported by previous studies.…”
Section: Pathological Subtypesmentioning
confidence: 99%